Analisis Nilai Tauhid dalam Nasheed ‘Sauqbilu Ya Khaliqi’: Kajian Sosiologi Sastra (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
This study aims to examine the representation of tawhid values in the lyrics of the nasheed Sauqbilu Ya Khaliqi and to explain their meanings through a literary sociology approach. This research employs a qualitative method with a descriptive design. The primary data source consists of the lyrics of the nasheed Sauqbilu Ya Khaliqi, while secondary data are obtained from books and relevant scientific literature. Data analysis was conducted through data reduction, data presentation, and conclusion drawing based on Sapardi Djoko Damono’s literary sociology theory. The findings reveal that the lyrics contain three dimensions of tawhid: tawhid rububiyah, tawhid uluhiyah, and tawhid asma’ wa shifat. Tawhid rububiyah appears in the recognition of Allah as the Creator and Sustainer of life. Tawhid uluhiyah is reflected in expressions of repentance, prayer, hope, and total devotion to Allah. Meanwhile, tawhid asma’ wa shifat is represented through references to Allah’s names and attributes, including Al-Khaliq, Al-Ghafur, Al-Wadud, and Ar-Rahim. A total of 13 representations of tawhid values were identified: six instances of rububiyah, four of uluhiyah, and three of asma’ wa shifat. From a literary sociology perspective, the nasheed functions not only as a personal spiritual expression but also as a cultural medium that strengthens Islamic religious identity and awareness of tawhid within Muslim communities.